Analisis Perilaku Wisatawan Pada Masa Pandemi Covid 19 - Hanif Mahendra Caniago; abdul Yusuf (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to find out, analyze and explain tourist behavior factors, tourist motivation factors, accessibility factors, lifestyle factors, and attraction factors that influence tourist behavior during the covid 19 pandemic, and to find out, analyze and explain which factors provide dominant influence on tourist behavior during the COVID-19 pandemic. The research method used is descriptive quantitative with data collection techniques using literature and online media, the population in this study is tourism visitors in Jakarta such as the Jaya Ancol Dream Park tour, the beautiful Indonesian mini park tour, the Ragunan zoo, and the Thousand Islands tour through the media. Instagram social media on the Eksplore_Jakarta account with a sample of 347 respondents, using a probability sampling technique using a simple random sampling technique because the sampling of population members is done randomly without regard to the strata in the population. And also simple random sampling is a technique to get a sample that is directly carried out on the sampling unit, data analysis using descriptive analysis and factor analysis. The data obtained from the respondents were processed with test aids using IMB SPSS 24. Based on the research results of the scale range analysis (descriptive) it can be explained that all instruments consisting of twenty-three (23) indicators located on the "s" scale bar or agree with the average score of 1449 and for factor analysis, the processed data shows that the eliminated 6 indicators because the communal value is less than 0.5 and as many as 17 indicators can be analyzed further, the total results are explained to get 2 factors formed, namely: the play factor with a total variance value of 31.7177%, the beauty factor with a total variance value of 26.397%. And the dominant factor that greatly influences tourist behavior during the COVID-19 pandemic is the play factor with a total variance value of 31.717%. Keywords: Tourist Behavior, Tourist Motivation Factors, Accessibility Factors, Lifestyle Factors, Attraction Factors, Games, Beauty.